Extensive Vulvectomy and Reconstructive Flaps for Advanced Vulvar Cancer in Young Woman: Case Reports - Malik, Nasdaldy; Soemanadi, M; Mukarramah, Dewi Aisiyah (http://dharmais.co.id/, 2023)
Introduction: : Vulvar cancer is a rare disease accounting for approximately 5% of female genital tract tumors worldwide. It is a squamous cell cancer that mostly affects older women over the age of 65. In the existing body of literature, no instances of vulvar cancer have been documented in the form of case reports. Therefore, this study aimed to report the challenges and outcomes of vulvectomy with reconstructive flap in vulvar cancer survivors in a 39-year-old woman. Case Presentation: A 39-year-old woman with a palpable lump around the vulva was present and being examined. The anatomic pathology report (APR) features suggested poorly differentiated malignant tumors. A neoadjuvant chemotherapy was then administered to the patient aimed at shrinking the size of the tumor. However, there was no effective response to the chemotherapy, which resulted in a progressive tumor. Extensive vulvectomy and reconstructive flap were carried out to support quality of life, and the outcomes were reported, including flap, survival, complications, and mortality. These outcomes were evaluated between November 2021 and March 2023. No total flap loss was observed, and neither was there any donor site morbidity or mortality during the process. Conclusions: This study showed that vulvar cancer was a rare condition at a young age. Advanced vulvar cancer was found in the patients and extensive vulvectomy surgery was carried out followed by a pedicled ALT flap. This option was currently the best for immediate reconstruction due to the preservation of sensibility and tissue availability in the donor areas. The result showed no wound dehiscence, marginal necrosis, or surgical site infection. After 15 months of follow-up, the flap was observed to have good vascularization. The association of the Gynecologist with the Plastic Surgeon offered palliative care to improve the quality of life of the patient and provide good postoperative results.